Sustainable Urban Cities: How to Design Livable Cities - Siddiqui, Wajiha; Siddiqui, Sadia; Mehdi, Muhammad; Qureshi, Muhammad Nafeel (MAJ - Malaysia Architectural Journal, 2025)
With over 55% of people living in cities worldwide, cities lack resources to cater to residents' basic needs. According to the UN-Habitat report, by 2050, around 68% of the world’s population will live in cities. The population density of South Asian cities, like Karachi, is estimated at 5779 people per square kilometer. Notably, areas affected by extreme weather occurrences are home to over 65% of Karachi's population. The unprecedented development, mass migration, illegal settlements, and land mafias have resulted in the expansion of informal and lower-income housing complexes. This puts forth a question about the sustainability of cities and whether cities can cater to the demands of the ever-expanding population while fulfilling the requirements for sustainable development. Given that 80 percent of the population lives on lots that are 120 square yards or less, the quality of life is not desirable. The metropolis is among the least livable cities as per the Economic Intelligence Unit’s Global Livability Ranking 2021. The huge housing demand overlooks livability when it comes to providing shelter to the urban poor. As a result, urban sprawl while resultant, does not serve the purpose. The continuous erosion of ecology and socially inappropriate housing complexes speak for themselves. Even though the demands of middle and upper-income groups are met by the architecture community, sustainability is catered at its face value. The essence of sustainability, which keeps social, economic, and ecological benefits in mind, is never taken into account for housing needs. This research analyzes the factors that can contribute to sustainable housing development without compromising on the ecology of the region, the social norms of the community, and the economic growth of the city. A mixed-methods approach examines the factors through multi-criteria decision-making methods to make the process efficient and consistent, and to achieve sustainable urban sprawl for livable cities.